Ruptures and resurgences: Marking the spatiality of transgender identity in India since the enactment of Transgender Persons Act 2019 - Gupta, Nikhil K. (Frontiers in Political Science, 2022)
This paper attempts to evaluate the social activism of the transgender groups on two plains- One, in terms of the uniqueness of the social movement and the areas which distinguishes it from the other social movements. It is interesting to note that what started as a purely identity based social movement has now acquired dimensions of redistributive justice. As a result of this transformation of the movement, there have started deliberations over securing a better set of rights and entitlements for the transgender groups as well. The second plain attempts to evaluate the achievements and advances made by the movement at the social and political fronts. This evaluation is necessary in order to appraise the trajectory of the movement which would foretell the direction of the movement and help in understanding the future scope and direction. The paper takes up three arguments in the context of the legal framework put in effect by the state. The first point of discussion is the effectiveness of the Transgender ID provided by the Transgender Persons Act and the possible challenges and loopholes related to it. While the state provides legal recognition through issuance of the transgender ID card, the same remains only a symbolic marker as the de facto identity remains unchanged, unless changed by the person oneself. The second point discuss the emerging rift amongst the transgender groups with respect to the reforms introduced recently. This rift has a tendency to pull in opposite direction causing tensions. The final aspect of my discussion relates to the subsequent challenges that emerge from the legal recognition of the transgender persons. These challenges touch upon the various aspects of legal, political, social and economic policy making and are inevitable for understanding the concerns of the transgender in India.